1993
DOI: 10.2214/ajr.161.3.8352119
|View full text |Cite
|
Sign up to set email alerts
|

Motion of the patella during walking: a video digital-fluoroscopic study in healthy volunteers.

Abstract: The purpose of this study was to determine the movements of the patella in relation to the other bones of the knee joint during normal walking. This is the first study we know of that uses radiographs to show these movements.SUBJECTS AND METHODS. Eight healthy adult volunteers with no previous cornplaints referable to the knee walked on a slowly moving treadmill while their patellae were imaged fluoroscopically in the anteroposterior plane with a Toshiba C-arm. Images were retrieved, transferred to radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…As compared to 20" of knee flexion, the bony congruence angle was more negative at 45" knee flexion, which was interpreted as a medial movement of the patella with increasing flexion, as described by Hefzy and Yang (1993), and Stein et al (1993).…”
Section: Discussionmentioning
confidence: 91%
“…As compared to 20" of knee flexion, the bony congruence angle was more negative at 45" knee flexion, which was interpreted as a medial movement of the patella with increasing flexion, as described by Hefzy and Yang (1993), and Stein et al (1993).…”
Section: Discussionmentioning
confidence: 91%
“…Sharp increase in force in anticipation of HS as the quadriceps muscles begin to contract to decelerate the leg in preparation for HS (Wallace et al, 1985;Stein et al, 1993;Crenna et al, 2001) and the fact that PFJ force has been shown to proportional to quadriceps activity (van Eijden et al, 1986).…”
Section: Simulation Model Control Strategymentioning
confidence: 99%
“…Differences in patellar kinematics have been observed between individuals with and without patellofemoral pain (MacIntyre et al, 2006), with patellofemoral pain with and without a brace (Draper et al, 2009), with anterior cruciate ligament deficiency or reconstruction (Shin et al, 2009) and with knee osteoarthritis and varus/valgus leg alignment (McWalter et al, 2007). Non-invasive methods for assessing patellar kinematics have been developed using imaging modalities such as fluoroscopy (Bey et al, 2008;Fregly et al, 2005;Stein et al, 1993), computed tomography (Pinar et al, 1994;Schutzer et al, 1986) and magnetic resonance imaging (MRI) (Fellows et al, 2005a;Patel et al, 2003;Powers et al, 1998;von Eisenhart-Rothe et al, 2004). One advantage of the MRI-based methods is that subjects are not exposed to ionizing radiation, which provides scope for longitudinal study designs.…”
Section: Introductionmentioning
confidence: 99%